2004
DOI: 10.1016/j.ijpharm.2004.02.032
|View full text |Cite
|
Sign up to set email alerts
|

Development of a controlled release formulation based on SLN and NLC for topical clotrimazole delivery

Abstract: Solid lipid nanoparticles (SLN) and nanostructured lipid carriers (NLC) are colloidal carrier systems providing controlled release profiles for many substances. Clotrimazole-loaded SLN and NLC were prepared by the hot high pressure homogenization technique in order to evaluate the physical stability of these particles, as well as the entrapment efficiency of this lipophilic drug and its in vitro release profile. The particle size was analyzed by PCS and LD showing that the particles remained in their colloidal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
217
2
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 589 publications
(234 citation statements)
references
References 12 publications
10
217
2
5
Order By: Relevance
“…The size of both systems remained stable during 90 days of storage. 22 Interestingly, the same research group published converse results, reporting that NLC was unstable over 90 days at room temperature and even at 4°C, while drug-loaded SLN was stable under both conditions. This might be attributed to the effect of the solid and liquid lipid types which were different from those in a previous study in which Compritol® 888 ATO and α-tocopherol were administered in preparing NLC instead of Dynasan® 116 and Miglyol® 812, respectively.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The size of both systems remained stable during 90 days of storage. 22 Interestingly, the same research group published converse results, reporting that NLC was unstable over 90 days at room temperature and even at 4°C, while drug-loaded SLN was stable under both conditions. This might be attributed to the effect of the solid and liquid lipid types which were different from those in a previous study in which Compritol® 888 ATO and α-tocopherol were administered in preparing NLC instead of Dynasan® 116 and Miglyol® 812, respectively.…”
Section: Introductionmentioning
confidence: 94%
“…21 They are prepared from one or blends of two or more solid lipids. 22 SLNs merge the superiorities of emulsions, liposomes, and polymeric nanoparticles. The solid matrix can preserve encapsulated drugs against chemical instability and provide controlled drug release patterns (compared to nanoemulsions).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the structure of SLNs protects labile drugs from degradation or oxidation by encapsulation (8)(9)(10)(11)17). TEAC experiments showed that the encapsulation in SLNs was successful in protecting Q10 from oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…SLNs have many advantages, especially for dermal applications such as occlusion, modulation of drug release and penetration into the skin (9). Since they are made from solid lipids, chemically unstable lipid soluble compounds that are sensitive to oxidation can be successfully encapsulated in the SLNs (8,10).…”
mentioning
confidence: 99%
“…27,28 SLNs give stable nanosuspension for an extended period of time in comparison with liposomes. 29,30 Furthermore, the SLNs are made of physiologically well-tolerated and generally recognized as safe (GRAS) excipients which reduce the cytotoxicity, leading to their wide variety of applications including dermal, oral, pulmonary, and intravenous use compared with polymeric nanoparticles. 26,31 The greatest benefit of SLNs is the possibility of their industrial scale production.…”
Section: -Azacytidine Was First Synthesized In 1963mentioning
confidence: 99%